2016
DOI: 10.1118/1.4964456
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to neutron dosimetry

Abstract: This work presents a novel, real-time, approach to workplace neutron dosimetry. It is believed that in the research presented in this paper, for the first time, a single instrument has been able to estimate effective dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Nonetheless, successfully implemented PSD is consistent with the claim of the preceding work where the same digitiser was tested with simulated neutron and gamma-ray pulses [39]. The digitiser was also utilised in a novel neutron survey meter, which further advocates the statement that good PSD results can be obtained with 150 MSps system [30].…”
Section: Jinst 12 P07023supporting
confidence: 77%
See 1 more Smart Citation
“…Nonetheless, successfully implemented PSD is consistent with the claim of the preceding work where the same digitiser was tested with simulated neutron and gamma-ray pulses [39]. The digitiser was also utilised in a novel neutron survey meter, which further advocates the statement that good PSD results can be obtained with 150 MSps system [30].…”
Section: Jinst 12 P07023supporting
confidence: 77%
“…Nonetheless, another study, conducted two years after the study by Flaska, successfully carried out crystal scintillator characterisation using 14-bit resolution, 200 MSps digitiser [13]. A digitiser of equal resolution and even lower sampling frequency (150 MSps) was effectively utilised to perform PSD for a neutron survey meter [30].…”
Section: Digitiser Selectionmentioning
confidence: 99%
“…Chen et al [3] and Levin and Narendra [4] demonstrated that nonlinear systems can be identified using neural networks. Furthermore, free open-source libraries such as the Fast Artificial Neural Network Library (FANN) [5] for network learning have already enabled researchers in various fields to use neural networks [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In fact, neural networks have recently been used for the identification of a wide range of nonlinear systems, including biological systems [23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%